Initial Load Stability of Different Trachea Suture Techniques: Tests on an Ex Vivo Model. (13th February 2018) - Kirschbaum, Andreas; Abing, Helen; Mirow, Nikolas
Abstract : Objective: Tracheal anastomosis can be performed with different suture techniques. In this experimental work, the resilience of anastomotic techniques to pressure and tensile stress was studied. Study Design: Ex vivo pig model. Setting: Experimental. Subjects and Methods: The trachea with the 2 main bronchi in freshly slaughtered pigs was isolated and intubated (CH 8.0). Both main bronchi were closed distally by a stapler. After resection of the trachea, an anastomosis (n = 15 per group) was created: group 1, single interrupted sutures; group 2, continuous running suture; group 3, mixed technique. A continuous tensile stress of 0, 500, 1000, or 1500 g was applied to the preparations. Mechanical ventilation with a maximum pressure of 70 mbar was initiated. The airtightness of the anastomosis was verified by submerging the entire preparation under water. Results: At tensile loads of 0.5 and 1.0 kg, all anastomoses created in the single‐stitch technique were airtight; at 1.5 kg, 93.3% were without leaks. In the continuous suture technique, the airtightness of anastomoses decreased with increasing tensile load: from 93.3% at 500 g to 73.3% at 1 kg and 66.6% at 1.5 kg ( P =. 02 at 1.5 kg). Anastomoses in the mixed technique were airtight in 80% at 500 g, 66.6% at 1 kg, and 46.6% at 1.5 kg ( P =. 01 in comparison with single stitches). Conclusion: Anastomoses created with single interrupted sutures showed the highest resilience against combined pressure and tensile stress.